Identification of carbonic anhydrase activity associated with protein complexes of photosynthetic membranes of spinach chloroplasts - Semenihin, A.V.; Zolotareva, E.K. (Reports of the National Academy of Sciences of Ukraine, 2014)
Protein complexes of photosynthetic membranes of spinach chloroplasts were separated by native charge shift electrophoresis after the solubilization of membranes by a non-ionic detergent digitonin. To determine the areas of the gel that contained the ATP synthase complex and its isolated catalytic part (CF1), the color reaction for ATFase activity was used. Due to the presence of cytochromes, the b6f thylakoid membrane complex was red in the unstained gel. The localization of cytochrome b6f complex, ATP synthase, and CF1 was confirmed by the subunit analysis of the corresponding protein zones by SDS-electrophoresis. Using nondenaturing electrophoresis followed by detection of carbonic anhydrase (CA) activity in the gel stained with bromothymol blue, the following carriers of CA were detected: photosystem II, cytochrome b6f complex, and ATP synthase. The data favor the assumption that multiple forms of thylakoid carbonic anhydrase take part in the internal proton transfer from the centers of their evolution to the ATP synthase.